DEVELOPMENT OF ANDROID-BASED DIMENSI APPLICATION AS A MEDIA FOR POETRY WRITING SKILLS FOR ELEMENTARY SCHOOL STUNDENTS - Adisa Adriani; Dadan Djuanda; Prana Dwija Iswara (Jurnal Cakrawala Pendas, 2024)
This research is motivated by the use of less than optimal media in Indonesian language learning, especially poetry material. This is because of the lack of creativity of teachers in utilizing technology and learning is only centered on textbooks so that students find it difficult to understand the learning materials delivered by teachers. The purpose of this research is to develop learning media in the form of an Android-based application "Dimensi". The research method used in this study is the Design and Development (D&D) method with the research design following the ADDIE (Analyze, Design, Develop, Implement, Evaluate) model. The subject of this study is grade V elementary school students with a total of 31 elementary school students in Rancaekek. The five research results according to the stages of ADDIE are as follows. 1) "Dimensi" media is developed based on an analysis of the needs of teachers and students, including the lack of learning media facilities that can support the learning process as a learning medium for poetry material in grade V of elementary school 2) The design stage is carried out by producing design components that will be contained in the "Dimensi" media, 3) The "Dimensi" media is developed using Kodular as the main application in the form of an android-based application (apk) with memory storage of 9.9 MB, 4) "Dimensi" media was implemented and evaluated through an expert validation test with an average percentage of 91% obtained by media experts, 93% by material experts, and 77%, 5) The results of student responses showed a percentage assessment of the Android application-based "Dimensi" media of 95% in the limited test and 92% in the broad test with very good criteria and can be used as a learning medium in the Indonesian content of class V poetry material for student.